A revision of the Iblidae and the stalked barnacles (Crustacea: Cirripedia: Thoracica), including new ordinal, familial and generic taxa, and two new species from New Zealand and Tasmanian waters - Buckeridge, John S.; Newman, William A. (Zootaxa, 2006)
The discovery of two diminutive and very distinct ibliform barnacles from shallow waters off northern New Zealand and northeastern Tasmania provides an opportunity to re-evaluate the Iblidae, the most primitive of the living thoracicans. These are retained within the Superorder Thoracica, but are distinguished at ordinal level from the remainder of the Pedunculata s.l. The resultant new order, the Ibliformes nov., comprises barnacles with predominantly chitinous rather than calcareous capitular plates; two families are recognized, the Iblidae s.s., comprising two subfamilies, the Iblinae (Ibla s.s.) and the Neoiblinae nov. (Neoibla gen. nov.), and the Idioiblidae nov. comprising the Idioiblinae nov. (Idioibla gen. nov.) and the Chaetolepadinae nov. (Chaetolepas Studer, 1889 and Chitinolepas gen. nov.). The monotypic Chitinolepas further highlights the high endemism and relict nature of the New Zealand marine fauna in particular and the southern hemisphere in general. On the basis of morphology and, where possible, genetic and larval work, it is recommended that the remainder of the stalked thoracicans be divided between three new orders, the †Cyprilepadiformes, Ibliformes, Lepadiformes and Scalpelliformes.